Internalized stigma and caregiver burden among caregivers of adolescents with non-suicidal self-injury: a moderated mediation analysis - Qin, Yuan; Yu, Ying; Liu, Jiao; Duan, Jiming; Liao, Huixia; Yang, Bo (Frontiers in Psychiatry, 2025)
BackgroundAdolescent non-suicidal self-injury (NSSI) constitutes a critical global health challenge, generating profound internalized stigma and familial burden among caregivers. However, the underlying mechanisms governing the relationship between these factors remain poorly understood.MethodsA cross-sectional survey was conducted. A sample of 385 caregivers of adolescents with NSSI completed the Internalized Stigma of Mental Illness Scale, Generalized Anxiety Disorder 7-Item Scale, Social Support Rating Scale, and Family Burden Scale of Disease. Moderated mediation analysis was employed to examine the dual mechanisms whereby anxiety mediates and social support moderates the stigma-to-burden pathway among caregivers.ResultsThe results revealed a pronounced direct effect of internalized stigma on caregiver burden (β = 0.265, p < 0.001) after adjusting for gender and age. Anxiety demonstrated partial mediation in this relationship (β = 0.254, p < 0.001), and social support significantly moderated the anxiety-mediated pathway (β = -0.007, p < 0.01), confirming convergent psychosocial pathways linking stigma to caregiver burden.ConclusionsThis study confirms a psychosocial pathway where internalized stigma exacerbates caregiver burden through anxiety-mediated mechanisms, while social support exerts moderated effects by mitigating anxiety’s mediating potency. These findings highlight the need for comprehensive strategies to reduce stigma, lower anxiety, and strengthen social support to break the cycle of ongoing stress for caregivers.